Pengaruh Financial Knowledge, Financial Self-Efficacy dan Financial Attitude terhadap Keputusan Penganggaran Modal: Studi Kasus UMKM di Bandar Lampung - Alya Febbyyana Basuki; Irawan Irawan; Sri Astuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Presently, several micro, little, and medium firms (MSMEs) encounter more intricate difficulties in financial management, particularly concerning efficient capital planning and allocation. Numerous business proprietors continue to struggle with the effective management of financial resources due to insufficient financial knowledge regarding principles, a lack of confidence in resource management, an unsupportive financial attitude, or reliance on misconceptions about finance. This study aims to examine the impact of financial knowledge, financial self-efficacy, and financial attitude on the capital budgeting decisions of micro, small, and medium enterprises (MSMEs) in Bandar Lampung. This research employs a quantitative methodology with primary data gathered from 401 respondents chosen via purposive sampling. Prior to the analysis of the data utilizing multiple linear regression with SPSS software, it underwent testing for validity, reliability, and classical assumptions. The findings indicated that financial knowledge, financial self-efficacy, and financial attitude exerted a positive and significant impact on capital budgeting decisions, both individually and collectively. The results affirm that the Theory of Planned Behavior is crucial in elucidating how knowledge, beliefs, and attitudes underpin rational, strategic, and sustainable decision-making for micro, small, and medium enterprises (MSMEs).